Pancasila Sebagai Sistem Etika: Implikasi Dalam Gaya Hidup Generasi Z Di Indonesia - Wahyuni Wahyuni; Ghisanie Azahra Alfyoni; Raynata Danielle Mulya; Amalia Putri Maharani; Chiatha Destalova Azzura; Raja Oloan Tumanggor (Journal on Education, 2024)
Pancasila as an ethical system has an important role in shaping the morality and behavior of Generation Z in Indonesia. However, the application of Pancasila values ​​by Generation Z is not yet optimal due to the influence of globalization and technological developments which make them more individualistic and tend to ignore Pancasila values. This research aims to identify the challenges faced by Generation Z in implementing Pancasila and the potential for its implementation through a modern approach that is relevant to their lifestyle. The method used is a literature study, which includes analysis from various sources such as journals and articles related to Pancasila values ​​and the younger generation. The research results show that even though the values ​​of Pancasila are starting to fade, there is a great opportunity to integrate these values ​​into the lives of Generation Z through technology-based education and digital social campaigns that suit their characteristics.